BRAND MANAGEMENT IN MODERN CONDITIONS: WARTIME CHALLENGES AND PERSPECTIVES - MELNYCHENKO, Oleksandr; MELNYCHENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The situation in which Ukrainian society currently finds itself due to the aggression of the Russian Federation requires quick and effective solutions from all participants in the economic process. Powerful Ukrainian brands are also forced to respond to an unprecedented situation. This article considers how brands respond to the challenges of wartime, what are the prospects for their development in this context. The purpose of the research is to identify effective branding strategies implemented in practice by 10 leading Ukrainian brands during the war period to determine the vector of their further development. Ten leading Ukrainian brands according to the 2021 rating were involved in the analysis of activities in wartime conditions. As a result of the analysis, it was found that not all brands respond to the challenges dictated by the situation and adjust their own brand strategies accordingly. Given the fact that each brand is the bearer of certain values that the company creates and affirms during its existence, the main task of the brand as the bearer of these values is to maintain and, if possible, increase customer loyalty. The analysis of the activities of leading Ukrainian brands during hostilities on the territory of Ukraine proves that the main brand strategy defined by the management was a reflection on military operations in Ukraine. It is actually about active reflection, i.e. direct participation in assistance, assistance to citizens, implementation of charitable projects that directly provide assistance to those who need it, etc. The second, no less important, brand strategy is the maximum digitization of the brand in order to provide services or deliver goods as quickly as possible. In wartime conditions, minimum clicks, simple interface, informative content to get any product or service becomes urgent, because the situation in which the customer is, and may find himself in, can suddenly change, so the sooner the customer gets the desired result, the better for all process participants. We see the promising development of brands in the maximum digitalization of offers, if not now, then in the post-war period, otherwise the brand will be lost among more promising competitors with digitalized offers. Further research should present the analysis of certain industries activities and their leading brands during the wartime in Ukraine.